FORMATION AND DEVELOPMENT OF A CROP GENEBANK IN THE REPUBLIC OF BELARUS - F. I. Privalov; S. I. Grib; I. S. Matys (Вавиловский журнал генетики и селекции)
The article overviews the main milestones of the researches on plant genetic resources in Belarus and presents the genetic bank, collected in the research institutions participating in the study and conservation of plant genetic resources in the Republic of Belarus. The results of the practical use of the global gene pool in crop breeding are shown.